PENINGKATAN HASIL BELAJAR IPAS MENGGUNAKAN MEDIA QUIZIZZ PADA SISWA KELAS IV SD NEGERI PEDURUNGAN LOR 01 - Nisrokhah; Sugiyanti; Siti Patonah; Juwariyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem with this study is the low learning outcome of students in class IV B SDN Pedurungan Lor 01. Teachers haven't used any interesting media in their learning. After the observation of the classroom, the reason for the poor learning outcome is that teachers are still conventionally using lecture learning methods and not using media in learning. It encourages researchers to use different and interesting media using the technology provided by the school, namely using quizizz media as a student evaluation material. This research is aimed at improving the learning outcomes of IPAS Class IV B SDN Pedurungan Lor 01. The type of research used is Class Action Research. (PTK). The data collection techniques used are observations, tests, and documentation. The classical learning outcomes of the students increased from the pre-cycle percentage of 22% of the cycle I gained 63% and cycle II gained 85%. The average learning outcome of the learners also increased. By the time the precycle gained an average of learning output of 57.4, Cycle I earned 75.2, and Cycle II earned 82.2. Research results show that the use of quizizz media for learning evaluation can improve student learning outcomes.